Removal of copper (II) ions from aqueous solution using acid- and alkali-treated carbonized mangosteen peel as adsorbent - Anee Sweatha; Krishnan Soundarajan (E3S Web of Conferences)
The level of toxic heavy metals from the industrial effluents, seeping into neighbouring waterbodies and agricultural land, must be reduced. Biosorption is a highly effective option. Fruit peels, a typical agricultural waste, have been widely employed as low-cost biosorbents. The purpose of this study is to investigate the removal of copper (Il) ions from aqueous solution using carbonized mangosteen peel. The aim of this research is to prepare the biosorbent, activate it with H2SO4 or KOH, carbonize the pulverized mangosteen peel and to optimize parameters such adsorbent dosage, agitation speed, initial metal-ion concentration, pH and contact time on percentage removal of Cu (II) ions. The adsorption isotherms have been studied using Langmuir and Freundlich isotherms, and the internal mass transfer coefficient has been investigated. Mangosteen peel was soaked in 5 mol% H2SO4 or 5 mol% KOH for one day, dried, and carbonized at 300°C for 30 min. Optimal conditions of 300 rpm agitation, initial metal-ion concentration 150 mg/L, 100 mg adsorbent dosage, pH 2 for H2SO4 treatment, 60 min contact time for maximum copper (II) ion uptake. The Freundlich isotherm model is found to fit the experimental data satisfactorily, with an R2 of 0.8273. The correlation coefficient of 0.9993 for pseudo-second-order model gives the best fit for kinetic data studied with an internal mass transfer coefficient of 0.9976.